Computational Mathematics and Modeling - Dmitriev, Vladimir; SpringerLink (Online service) (New York : Springer US : Imprint: Springer.)
Computational Mathematics and Modeling focuses on important Russian contributions to computational mathematics that are useful to the applied scientist or engineer. This quarterly publication presents timely research articles by scientists from Moscow State University, an institution recognized worldwide for influential contributions to this subject. Numerical analysis, control theory, and the interplay of modeling and computational mathematics are among the featured topics.
Keywords: Applied mathematics; Engineering mathematics; Computer mathematics; Mathematical models; Mathematical optimization; Mathematical Modeling and Industrial Mathematics; Computational Mathematics and Numerical Analysis; Applications of Mathematics; Optimization